Evaluation of Tidal Energy Potential Using a Two-Way Tidal Energy Model - Rusvan, A. Aliffathur; Maricar, Farouk; Thaha, M. Arsyad; Paotonan, Chairul (Salehan Institute of Higher Education, 2024)
Tidal energy is a renewable energy source that provides sustainable energy through the utilization of tidal differences, making it a very promising option. This study examines a more effective tidal energy reservoir model by building a 1:100 scale prototype in the laboratory with several predetermined variations, namely an earthen pond (100, 80, and 60 cm), and flow holes (1.5, 1, and 0.5 cm) with initial tidal height differences of 10 cm, 15 cm, and 20 cm. The model uses a 6-hour time period, which corresponds to a semidiurnal tidal model. The results showed that the highest energy output was 281.84 kWh, achieved with a 1.5 cm flow hole, 20 cm tidal height difference for the initial condition, and 80 cm pond width. For a 1 cm flow hole, the outputs were 1774.8 kWh and 1803.78 kWh for 15 cm and 20 cm tidal height difference for the initial condition with a pond width of 100 cm. Meanwhile, the 0.5 cm flow hole produces potential energy outputs of 2623.8 kWh and 2611.4 kWh for different tidal heights of 15 cm and 20 cm for the initial condition with a pond width of 100 cm. Better model performance can be connected to a mini generator to validate the energy generated from the designed prototype model. Doi: 10.28991/CEJ-2024-010-09-016 Full Text: PDF